Characterization and modeling the effect of temperature on power HBTs InGaP/GaAs - Mokeddem Nadjet; Ghaffour Kheireddine (Institute of Advanced Engineering and Science, 2020)
The variation and stability of HBT’s parameters at different temperatures are important for utilizing these devices in high-power integrated circuits. The temperature dependence of the DC current gain of bipolar transistors, as a key device parameter, has been extensively investigated. A major issue of the power HBT’s is that the current gain is decreased with junction temperature due to self-heating effect. Hence, how to stabilize the DC current gain and RF performances is important issue to develop the power HBTs. This work describes the DC and high-frequency temperature dependence of InGaP/GaAs HBT’s. The substrate temperature (T) was varied from 25 to 150°C. The static and dynamic performances of the HBT are degraded at high temperature, due to the reduced of carrier mobility with increasing temperature. The current gain (β) decreases at high temperatures; from 140 to 127 at 25 to 150°C, while the decreases in the peak Ft and Fmax are observed from about 110 GHz to 68 GHz and from 165 GHz to 53 GHz respectively in the temperature range of 25 to 150°C.